Development of Synthetic Unit Hydrograph Parameters from the Influence of Watershed Form Factor - Hayati, Maulida; Montarcih Limantara, Lily; Prasetyorini, Linda (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2026)
The Synthetic Unit Hydrograph (HSS) is a predictive model used in hydrological analysis to estimate river flow response due to design rainfall, playing an important role in water infrastructure planning and flood mitigation strategies. This study aims to develop HSS parameters by quantitatively analyzing the relationships between the Watershed Form Factor (FD), peak discharge (Qp), and peak time (Tp). The study covered 10 watersheds on Java Island, which were selected to represent a wider and more diverse range of hydrological characteristics. The methods used include morphometric analysis to determine FD as a ratio between the area and perimeter of the watershed, hydrograph analysis to obtain unit hydrographs in each watershed/subwatershed, and statistical correlation analysis to examine the relationship between FD and hydrographs. The results showed that FD has a significant negative linear relationship with Qp (R = -0.802) and Tp (R = -0.820), indicating that the larger the watershed shape, the smaller the FD value, leading to an increase in peak discharge and peak time. This finding has significant implications for the development of the SUH model, particularly in watersheds with limited hydrological data. By including FD in the SUH parameter formulation, hydrograph estimation becomes more accurate, supports water resources planning, and improves the effectiveness of flood mitigation strategies and drainage system design.